ESTIMATION OF THE INFLUENCE OF EARTHQUAKE ON STABILITY OF THE SOUTHERN COAST OF THE CASPIAN SEA (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
In this work the analysis of geological structure, tectonics, morphology of the southern coast of the Caspian Sea for the purpose of microseismic division into districts and engineering-geological division into districts on susceptibility of territories to landslides and quicksand processes are resulted. Data are processed in the environment of GIS.
Keywords: Caspian Sea; landslides and quicksand processes; GIS